The best trigonometric and bilinear approximations for functions of many variables from the classes B^r_p, θ. II - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The order estimates are obtained for the best trigonometric and bilinear approximations of the classes B^r_p, θ of functions of many variables with respect to the metric L_q when p and q satisfy certain relations.